Enhancing academic development: a reflexive exploration of staff and students’ experiences on curriculum co-creation - Sebolao, Rosaline Raseboya (OpenED Network, 2023)
Academic development of students and staff is a critical element in higher education, especially with reference to their engagement in curriculum development. While higher education institutions advocate for the inclusion of students in curriculum co-creation, in practice, this has not been easily implemented. The urgency to create this collaborative ecosystem necessitates a reflexive contribution. In this article, I explore the experiences of academic staff and students on their engagement in curriculum co-creation with a specific focus on developing a study guide for the newly developed module, which is part of the decolonisation process. The emphasis on meta-cognitive skills and the social justice element in the curriculum development process ensures a responsive curriculum that meets the needs of society, students and staff in a cohesive and integrated manner. I underpin this reflective study on Schon’s theory of reflection on action. I argue that engaging students in curriculum creation stimulates deep learning, an empowerment attribute which I explore as it enhances innovative and critical thinking. This study employed qualitative methods of collecting and analysing data, followed by identifying important themes from the data. The reflections and emergent themes provide pathways to enhance academic development to encourage curricula co-creation processes in higher education.
Keywords: Academic development; Co-creation; Curriculum; Decolonisation; Scholarship of Teaching; Learning